Development of Islamic-Science Integrated Physics E-Module To Build the Character Profile of Pancasila Students for High School Students - Raharjo, Semiono; Puspita, Yenda (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
The Pancasila student profile (PSP) is a form of translation of the national education system. One of the PSP dimension characters is faith, piety to God Almighty, and noble character. Educators need to implement the PSP dimension thoroughly from early childhood education so that each learner becomes a competent lifelong learner, has character, and behaves according to the values of Pancasila. This can be realized of them by using integrated e-module teaching materials. This research aims to develop Islamic-Science integrated e-module teaching materials that are valid, practical, and effective for building PSP characters of high school students. The type of research used is research and development. The research instrument used a validation sheet, observation of learning implementation, student response questionnaire, and pre-test and post-test questions. The trial was conducted in class X with a total of 36 students. The results of the study obtained validity with a very valid category, for practicality based on the results of observations obtained with excellent qualifications, while for effectiveness seen from the N-gain test pre-test and post-test increased with an average of 0.70 in the medium category and received a positive response from the analysis of the students’ questionnaire. These results indicate that the Islamic science integrated e-module for building the PSP character of high school students has met the valid, practical, and effective criteria.